2020
DOI: 10.1097/j.pain.0000000000002161
|View full text |Cite
|
Sign up to set email alerts
|

Developing clinical prediction models for nonrecovery in older patients seeking care for back pain: the back complaints in the elders prospective cohort study

Abstract: Three clinical prediction models were developed for nonrecovery in older adults seeking care for back pain; the model predicting persistent disability performed best (optimism-adjusted R 2 46%, area under the curve 0.85).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 64 publications
(139 reference statements)
0
15
1
Order By: Relevance
“…Comorbidity has previously been associated with the clinical course of a back pain episode in older adults and can thus be considered a promising prognostic factor. 5,30,51,54,57,65 Comorbidity was defined by Feinstein as “any distinct additional entity that has existed or may occur during the clinical course of a patient who has the index disease under study.” 8 Comorbidity is common in people with back pain, and the prevalence of 2 or more coexisting conditions increases with age. 14,18,34 Moreover, the presence of comorbidities is associated with increased personal and societal economic burden from back pain, and with lower compliance to clinical practice guidelines by healthcare providers.…”
Section: Introductionmentioning
confidence: 99%
“…Comorbidity has previously been associated with the clinical course of a back pain episode in older adults and can thus be considered a promising prognostic factor. 5,30,51,54,57,65 Comorbidity was defined by Feinstein as “any distinct additional entity that has existed or may occur during the clinical course of a patient who has the index disease under study.” 8 Comorbidity is common in people with back pain, and the prevalence of 2 or more coexisting conditions increases with age. 14,18,34 Moreover, the presence of comorbidities is associated with increased personal and societal economic burden from back pain, and with lower compliance to clinical practice guidelines by healthcare providers.…”
Section: Introductionmentioning
confidence: 99%
“…Given multiple factors (eg, psychological and physical comorbidities, maladaptive coping, and age-related physical problems) can modify the LBP experience in older adults. 47,50 Physical function is a core outcome domain for patients with LBP. 6,24,43,51 International consensus recommends using the Roland-Morris Disability Questionnaire (RMDQ) or the Oswestry Disability Index (ODI) to measure physical function in clinical trials.…”
mentioning
confidence: 99%
“…One population-based cohort and one primary care cohort reported that self-reported morning stiffness is clearly associated with features of spinal OA (22,23). Interestingly, whereas painful range of motion has recently been found to be associated with poor prognosis of back pain (24), it did not reach consensus in this Delphi process to be included in a symptomatic definition of spinal OA. These results suggest discerning levels of pain severity for both the structural aspects and symptoms.…”
Section: Discussionmentioning
confidence: 99%